The Grotesque Sublime: Play with Terror - Shun-liang Chao (University of Edinburgh, 2006)
Throughout "La Préface de Cromwell" (1827), Victor Hugo treats the sublime and the grotesque as different realms without seriously expounding upon their distinction. In examining the major treatises of the sublime, however, one will find that the grotesque actually resides inside the sublime in terms of evoking violent emotions, especially terror. This essay, then, aims to bring into relief the essential similarities between the grotesque and the sublime, thereby drawing attention to the role of the grotesque in the construction of artistic or aesthetic modernity.